Andrzej Olszowski jako fundator kościoła w Ujeździe: Andrzej Olszowski as the founder of the church in Ujazd - Gliński, Waldemar (Prace Polonistyczne, 2019)
In the 1420s, during the founding of Ujazd, the first church was built. It was a wooden church. It survived until 1794. The construction of the second temple was initiated by Primate Andrzej Olszowski. It was built in 1674–1680. Its architecture is typical of the wall-pillar construction popular in the 17th century. It was characterized by pillars embedded in the single-nave interior. Comparative analysis indicates the Warsaw architectural center as the provenance of this temple, whose representative objects were the buildings of Giovanni Battista Gisleni. Gisleni belonged to the most prominent architects of the Polish Baroque. He was active in the court of Sigismund III, Władysław IV and Jan Kazimierz. Primate Olszowski therefore had to meet him personally. In 1694, the church was consecrated by the grandson of Kacper Denhoff – Bishop of Przemyśl, and later by the Grand Chancellor of the Crown, Jerzy Albrecht Denhoff.